Harnessing slaughterhouse by-products: From wastes to high-added value natural food preservative. (30th January 2020) - Przybylski, Rémi; Bazinet, Laurent; Firdaous, Loubna; Kouach, Mostafa; Goossens, Jean-François; Dhulster, Pascal; Nedjar, Naïma
Abstract: Blood, from slaughterhouses, is an inevitable part of meat production, causing environmental problems due to the large volumes recovered and its low valorization. However, the α137–141 peptide, a natural antimicrobial peptide, can be obtained after hydrolysis of hemoglobin, the main constituent of blood red part. To recover it at a sufficient concentration for antimicrobial applications, a new sustainable technology, called electrodialysis with ultrafiltration membrane (EDUF), was investigated. The α137–141 concentration was increased about 4-fold at a feed peptide concentration of 8% with an enrichment factor above 24-fold. This feed peptide concentration also needed the lowest relative energy consumption. Moreover, this peptide fraction protected meat against microbial growth, as well as rancidity, during 14 days under refrigeration. This peptide fraction was validated as a natural preservative and substitute for synthetic additives against food spoilage. Finally, producing antimicrobial/antioxidant peptide from wastes by EDUF fits perfectly with the concept of circular economy. Highlights: EDUF is an ecoefficient method to valorize slaughterhouse by-products. EDUF uses no solvent or toxic chemical for direct food application. EDUF offers an eco-friendly way to produce natural preservatives for meat. EDUF is very selective, and can separate one specific peptide from one hundred peptides.